2019
DOI: 10.1126/science.aau9952
|View full text |Cite
|
Sign up to set email alerts
|

Branch-restricted localization of phosphatase Prl-1 specifies axonal synaptogenesis domains

Abstract: Central nervous system (CNS) circuit development requires subcellular control of synapse formation and patterning of synapse abundance. We identified the Drosophila membrane-anchored phosphatase of regenerating liver (Prl-1) as an axon-intrinsic factor that promotes synapse formation in a spatially restricted fashion. The loss of Prl-1 in mechanosensory neurons reduced the number of CNS presynapses localized on a single axon collateral and organized as a terminal arbor. Flies lacking all Prl-1 protein had loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 63 publications
3
44
1
Order By: Relevance
“…Fig 5), whereas inhibition of ezrin function by the small molecule compound NSC668394 caused more and larger blebs to form (Supp Fig 6). Additionally, the recent finding that knockout of a different phosphatase with activity for ezrin decreases protrusion in neurons in vivo supports the role of ezrin dephosphorylation in protrusion initiation (26). Compared to cells expressing wildtype ezrin, osteosarcoma cells expressing the T567D mutant exhibit fewer protrusions (Fig.…”
supporting
confidence: 53%
“…Fig 5), whereas inhibition of ezrin function by the small molecule compound NSC668394 caused more and larger blebs to form (Supp Fig 6). Additionally, the recent finding that knockout of a different phosphatase with activity for ezrin decreases protrusion in neurons in vivo supports the role of ezrin dephosphorylation in protrusion initiation (26). Compared to cells expressing wildtype ezrin, osteosarcoma cells expressing the T567D mutant exhibit fewer protrusions (Fig.…”
supporting
confidence: 53%
“…Decreased gene expressions of Ptp4a1 along with other cAMP response element‐binding protein (CREB)‐dependent genes were seen in the hippocampus of trained APP Sw,Ind mice, which were associated with early memory loss [16]. Further evidence demonstrated that PTP4A1 (also known as phosphatase of regenerating liver‐1) was important for synapse formation via modulation of insulin receptor‐Akt signaling in Drosophila ; loss of phosphatase of regenerating liver‐1 resulted in locomotor deficiencies and decreased numbers of synapses [17]. Therefore, dysregulation of PTP4A1 may directly cause the loss of synapses leading to the memory loss characteristic of AD dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular regulation may involve protein interaction or posttranslational modifications or local protein translation at the rear of a migrating cell. In line with local translation, the Drosophila axonal synaptogenesis domains are specified by branch-restricted localization of the membrane-anchored phosphatase of regenerating liver (Prl-1), and the spatial restriction of Prl-1 requires untranslated sequences in its messenger RNA (32).…”
Section: Discussionmentioning
confidence: 99%